Operation and Sensitivity Analysis of a Micro-Scale Hybrid Trigeneration System Integrating a Water Steam Cycle and Wind Turbine under Different Reference Scenarios - Rafał Figaj; Krzysztof Sornek; Szymon Podlasek; Maciej Żołądek (Energies, 2020)
Renewable energy sources, such as solar, wind, biomass, and geothermal energy, are being more and more adopted in small and micro-scale distributed generation systems. In this context, different hybrid configurations and layouts that may adopt, lead to different energy and economic performance of energy generation systems. In micro-scale applications, biomass and solar energy sources are more frequently investigated in literature compared to other combinations as biomass and wind energy. The analysis of the performance of a novel small-scale trigeneration system is presented in this paper. The system includes biomass boiler, water steam turbine, absorption chiller, and wind turbine, and it is linked to the electric grid by means of a bidirectional connection, allowing to the store virtually the electrical energy produced in excess, and use when needed. For the proposed system, a zootechnical farm and a residential building are considered as case study, including different scenarios for the reference energy system. The Transient System Simulation (TRNSYS software is used to model, simulate, and investigate the system performance under realistic operation conditions. Energy and economic performance of the system is assessed by means of a daily, weekly, and yearly analysis. The effect of the main design parameters, as steam and wind turbine power on the system performance, is investigated by means of a sensitivity analysis. The investigations show that the Simple Pay Back time of the proposed system is below 6 years, when the biomass is free, capacities of steam and wind turbines lower than 4 kW are selected, and a reference system with a natural gas boiler and electrical grid is considered. The system allows one to achieve satisfactory energy and economic performance under the considered conditions, when a proper design of the system component capacities is adopted.